Preliminary Assessment of the Generative Potential of Crude Oil Samples From Three (3) Offshore Exploration Oil Wells in Nigeria (Journal of Basic and Applied Research in Biomedicine, 2022)
Oil generating potential of virgin crude oil samples procured from wells within the Southern part of Nigeria was employed in this study. The work aimed at characterizing the organic matter, determining the quality, analyzing the quality status as well as highlighting the source input for the purpose of deducing the hydrocarbon potential of the crude oil sample. The crude fractions were eluted using n-hexane for Saturated Hydrocarbons (SHC), methyl-benzene for Aromatic Hydrocarbons (AHC), benzene / ethyl acetate (3:1) for Vanadyl Porphyrins (VOP), dichloromethane / n-hexane (2:3) for Nikel Porphyrins and methanol / dichloromethane (2:1) for Nitrogen, Sulphur and Oxygen compounds (NSO).  The Yorla oils had the lowest VOP / NIP ratios and NSO values which ranged from 0.1 – 0.8 with an average of 0.46 ± 0.20 and 0.1 – 0.3 with an average of 0.16 ± 0.1 respectively. This indicated that the Yorla oil was more matured and has a higher quality as compared to the Usari oils   and Oloibiri oils which was slightly degraded. The Total Petroleum Hydrocarbon (TPH) of the samples was relatively high, this implies that the source rocks of the oils is Type 1 Kerogen and therefore, is oil prone. The very high values of the SHC/AHC ratios of the oil showed that the oils are not degraded and have high quality. It can be concluded that the sediments of the oils posses a hydrogen rich organic matter. The source rocks of the oils have the potentials to generate oil if given sufficient maturity time.